PEMANFAATAN AUDIO RECORDING EQUIPMENT DALAM PEMBELAJARAN PRAKTIK INSTRUMEN REBAB, KENDANG DAN GENDER - Wahyu Thoyyib Pambayun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
This research is entitled "Utilization of Audio Recording Equipment in Practical Learning of Rebab, Kendang and Gender Instrument." The problems described in this study are: how are the types of audio recording equipment that can be used in learning the practice of fiddle, drum, and gender instrument, how to set and use audio recording equipment, and how to use audio recording equipment in learning the practice of fiddle, drums, and gender instrument. This research is qualitative research that uses descriptive analysis research methods. Data were collected by means of observation, literature study, and interviews. The data analysis technique used includes four stages: data collection, data reduction, data display, and concluding. The purpose of this study is to provide recommendations for types of audio recording equipment that can be used in learning the practice of fiddle, drum, and gender instrument, provide an understanding of how to set and use audio recording equipment, as well as provide an understanding of how to use audio recording equipment in learning the practice of the fiddle instrument. Drums and gender.